MicroRNA let-7i inhibits granulosa-luteal cell proliferation and oestradiol biosynthesis by directly targeting IMP2. Issue 5 (May 2022) - Xu, Xiao; Shen, Hao-Ran; Yu, Min; Du, Mei-Rong; Li, Xue-Lian
Abstract: Research question: Increased granulosa cell division is associated with abnormal folliculogenesis in polycystic ovary syndrome (PCOS). Lethal-7i microRNA (let-7i) may play an important role in the follicular development and granulosa cell growth; therefore is let-7i involved in PCOS pathogenesis? Design: The expression of let-7i was measured in granulosa-luteal cells (GLC) from women with or without PCOS. A human granulosa cell line, KGN, was used for the functional study. Mimics and inhibitors of let-7i, lentiviruses expressing insulin-like growth factor 2 mRNA binding protein (IMP2), and small-interfering RNAs were transfected into KGN cells. KGN cell proliferation was determined by 5-ethynyl-2′-deoxyuridine (EdU) and Cell Counting Kit-8 (CCK-8) assays. The cell cycle and apoptosis were assessed by propidium iodide-annexin V (PI-A) staining and fluorescence-activated cell sorting. Oestradiol concentration was determined by enzyme-linked immunoassay. Bioinformatics analysis and luciferase reporter assay were applied to confirm the let-7i target genes. Results: The study showed that let-7i was down-regulated in PCOS GLC ( P  = 0.001). Mimics of let-7i inhibited KGN proliferation ( P  = 0.001), and decreased aromatase expression ( P  = 0.030) and oestradiol production ( P  = 0.029), whereas let-7i inhibitors had the opposite effect. Bioinformatics analysis and quantitative real-time (qRT) PCR identified IMP2 as a target of let-7i ( P  = 0.021). qRT-PCR and western blot analysis indicated that IMP2 was up-regulated in GLC in women with PCOS ( P  = 0.001 and P  = 0.044), and IMP2 expression was suppressed by let-7i in KGN cells ( P  < 0.001). Luciferase reporter assay results ( P  = 0.002), combined with the rescue assay, confirmed that let-7i inhibited KGN cell proliferation and reduced oestradiol concentration by directly targeting IMP2. Conclusions: let-7i was down-regulated in PCOS GLC. Overexpression of let-7i inhibited KGN cell proliferation and decreased oestradiol production in an IMP2-dependent manner, providing a new molecular mechanism for PCOS.